" In-Vitro and Radiographic Study to Investigate the Presence of Second Mesio-Buccle Canal (MB2) in Second Upper Primary Molar Using Dental Microscope and (CBCT)" (Journal of Hama University, 2021)
Aims and Objectives: To determine the frequency of second mesiobuccal canal (MB2) in Second Upper Primary Molar by using dental microscope and (CBCT) ,and to determine the accuracy of each method in its detection. Materials and Methods: The research sample consisted of 150 extracted second upper primary molars with access cavities and were investigated the presence of second mesio-buccle (MB2) canal by using dental microscope. Molars that have not detecting the mesio-buccle canal inside it were examined by CBCT. Results: This study showed that the overall frequency of MB2 in second upper primary molar when examing using CBCT (97.3%) was higher than microscope (82%). Conclusion: The use of multiple methods is preferred to detect the presence of (MB2) canal in second upper primary molar.